(untitled) (Journal of English Language Teaching and Education (JELTE), 2024)
This descriptive quantitative study was conducted to analyze students’ anxiety when speaking English. The subjects in this study were class A students in the second semester of IKIP PGRI Pontianak for the academic year 2021/2022. This sample was selected using a purposive sampling technique. Data collection techniques applied in this study were indirect communication using PSCAS questionnaires and direct communication using interviews. Questionnaires are used to determine the level of students’ anxiety when speaking. Meanwhile, interviews were used to find out the causes of students’ anxiety when speaking. Based on the results of the PSCAS questionnaire, the level of speaking anxiety in class A Morning in the second semester is divided into three levels, namely; 52% at moderate level, 27% at high level and 21% at low level. It can be concluded that the level of anxiety speaking English in class A Morning in the second semester is at a moderate level with 52%. Based on the results of the interviews, it can also be concluded that the causes of anxiety experienced by students when speaking are due to lack of preparation, shyness, lack of self-confidence, embarrassment, lack of vocabulary, friends/classmates, and fear of making mistakes. Keyword: Speaking Anxiety, Analysis Anxiety, PSCAS Questionnaire